Ozone pollution influences soil carbon and nitrogen sequestration and aggregate composition in paddy soils - Kou, Taiji; Wang, Lirui; Zhu, Jianguo; Xie, Zubin; Wang, Yanling (Plant and soil, 2014)
Background and aims Much attention has focused on the effects of tropospheric ozone (O₃) on terrestrial ecosystems and plant growth. Since O₃ pollution is currently an issue in China and many parts of the world, understanding the effects of elevated O₃ on soil carbon (C) and nitrogen (N) sequestration is essential for efforts to predict C and N cycles in terrestrial ecosystems under predicted increases in O₃. Thus the main objective of this study was to determine whether an increases in atmospheric O₃ concentration influenced soil organic C (SOC) and N sequestration. Methods A free-air O₃ enrichment (O₃-FACE) experiment was started in 2007 and used continuous O₃ exposure from March to November each year during crop growth stage in a rice (Oryza sativa L.)—wheat (Triticum aestivum L.) rotation field in the Jiangsu Province, China. We investigated differences in SOC and N and soil aggregate composition in both elevated and ambient O₃ conditions. Results Elevated atmospheric O₃ (18-80 nmol mol⁻¹ or 50% above the ambient) decreased the SOC and N concentration in the 0-20 cm soil layer after 5 years. Elevated O₃ significantly decreased the SOC concentration by 17% and 5.6% in the 0-3 cm and the 10-20 cm layers, respectively. Elevated O₃ significantly decreased the N concentration by 8.2-27.8% in three layers at the 20 cm depth. In addition, elevated O₃ influenced the formation and transformation of soil aggregates and the distribution of SOC and N in the aggregates across soil layer classes. Elevated O₃ significantly decreased the macro-sized aggregate fraction (16.8%) and associated C and N (0.5 g kg⁻¹ and 0.32 g kg⁻¹, respectively), and significantly increased the silt+clay-sized aggregate fraction (61%) and associated C (1.7 g kg⁻¹) in the 0-3 cm layer. Elevated O₃ significantly decreased the macro-sized aggregate fraction (9.6%) and associated C and N (1.4 g kg⁻¹ and 0.35 g kg⁻¹, respectively), and significantly increased the silt+clay-sized aggregate fraction (41.8%) and decreased the corresponding associated N (0.14 g kg⁻¹) in the 3-10 cm layer. Elevated O₃ did not significantly effect the formation and transformation of aggregates in the 10-20 cm layer, yet it did significantly increase the C concentration in the macro-sized fraction (1 g kg⁻¹) and decrease the N concentration in the macro-and micro-sized fractions (0.24 g kg⁻¹ and 0.16 g kg⁻¹, respectively). Conclusion Long-term exposure to elevated atmospheric O 3 negatively affected the physical structure of the soil and impaired soil C and N sequestration.